Extended Neuralgic Amyotrophy Syndrome in a Confirmed COVID-19 Patient After Intensive Care Unit and Inpatient Rehabilitation Stay. (August 2021) - Alvarez, Armando; Amirianfar, Edwin; Mason, Marisa Carino; Huang, Laura; Jose, Jean; Tiu, Timothy
Abstract : Abstract: The cause of neuralgic amyotrophy is often unknown but is commonly associated with a recent upper respiratory viral tract infection. Since the beginning of the COVID-19 pandemic, there has been a tireless effort to understand the sequelae of the virus. A 46-yr-old woman who presented after a COVID-19 hospitalization complicated by hypoxic respiratory failure requiring intubation and mechanical ventilation for 23 days was subsequently found to have lower limb sensorium changes as well as upper limb weakness. Left shoulder abduction and extension were both 3/5 in motor strength, and left hip flexion strength was 4/5 with diminished sensation to crude touch in the left lateral thigh. Nerve conduction studies and electromyography findings included a mild left median neuropathy at the wrist and motor unit recruitment pattern consistent with a chronic left upper trunk plexopathy with reinnervation. The case presented describes an extended neuralgic amyotrophy syndrome from an atraumatic mechanism in a previously diagnosed COVID-19 patient. An extended neuralgic amyotrophy syndrome has at least three immune mediated etiologies postulated (1) direct neuropathogenicity, (2) molecular mimicry, and (3) direct cytotoxic effects on peripheral nerves. As COVID-19 survivors continue to be seen in outpatient settings, practitioners should remain aware of diffuse neurological complications as sequelae of the virus persist. Abstract : Supplemental digital content is available in the text.